Advancing students’ reading literacy through the development of website-based multimodal instructional content - Sukarno Sukarno; Sri Haryati; Siswanto Siswanto; Rolisda Yosintha; Candradewi Wahyu Anggraeni (LPMPP Universitas Negeri Yogyakarta, 2026)
This study aimed to develop website-based multimodal instructional content to enhance the literacy competency of junior high school students in Indonesia. The study conducted developmental research adopting the ADDIE framework (analysis, design, development, implementation, and evaluation). In the analysis phase, it involved analyzing the educational needs and content through interviews with certified junior high school teachers and literacy experts. The design phase dealt with designing a reading-focused website, learning content, and assessment tools that were based on the analysis of learning goals, competencies, and study materials. In the development phase, it included feasibility testing of the developed website using the Fuzzy Delphi method with 10 experts, content validation with 5 experts, and instrument validation with 5 experts. In the implementation phase, the product was scrutinized through a quasi-experimental design to reveal its effectiveness. In the evaluation stage, it was conducted to evaluate the results of analysis, design, feasibility, and implementation of educational websites, learning content, and instruments. The Fuzzy Delphi method demonstrated that the reading literacy competence, linguistic features, and presentation met established validity and feasibility criteria, affirming the appropriateness of the developed content for instructional use. The empirical testing revealed that website-based multimodal instructional content is effective in enhancing students’ reading literacy competence.